Dampak Aplikasi Foaming Agent pada Tanah Gambut Bekas Terbakar di Desa Rimba Panjang, Kabupaten Kampar, Provinsi Riau - Pratiwi Dwi Susanti; Basuki Wasis; Bambang Hero Saharjo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Peat land fire decreases the thickness of peat soil (subsidence) and damage the physical, chemical, and biological properties of the soil. Forest and land fires extinguishing is usually be managed using water and tend to take a very long time until the fire is completely quenched. Extinguishing using water in a peat land is deemed less effective and less efficient because of the process of fuel temperature reduction that is not directly completed regarding the water evaporation due to the high fire temperature on the surface. Moreover, using a foaming agent from palm oil, is a new method of fire extinguishing. This method was done by extinguishing the fire using a fire extinguisher tool that was filled with a mixture of NF46 0,5 100 L m-² solution. The direct extinguishing was carried out on the plot and the extinguishing time length was analyzed until the fire or smoke on the plot was no longer visible, then being left for a day. Based on the analysis results, the extinguishing using a foaming agent for three months does not damage the ecosystem and even does not have a detrimental impact on plant growth within three months. Besides, extinguishing using a foaming agent can speed up the extinguishing process (3 until 4,6 minute) compared to using water (50 minute).